Analisis Opini Publik pada Peraturan Menteri Perdagangan Republik Indonesia Nomor 31 Tahun 2023 Tentang Penutupan Tiktok Shop di Indonesia - Lestari, Wahyu Ikke Siswika; Dewi, Dian Suluh Kusuma (Universitas Medan Area, 2024)
This article aims to analyze public opinion using agenda-setting theory obtained from the TikTok Shop closure incident that occurred on the social media platform Twitter. This research uses a qualitative descriptive research method by referring to literature studies, theoretical studies, information from news portals such as kompas.com, CNN Indonesia and other sources, as well as data obtained from Twitter social media which is then processed using the Nvivo 14 application. automated coding and analyzed using word cloud and hierarchical diagram analysis features. The policy process for closing the TikTok shop has become a topic of debate on various social media, including Twitter. Therefore, social media Twitter has become a platform for determining the public opinion agenda regarding the issue of closing the TikTok shop. The results of this research show that public opinion on the social media platform Twitter is influenced by the agenda-setting theory and these results are under the research findings and the impact felt regarding the closure of the TikTok Shop.